Acute Ulcerative Enterocolitis With Severe Protein Loss Due to Mucosal Invasion With Enterococcus spp. in a Dog With Exocrine Pancreatic Insufficiency: A Case Report - Cartwright, Jennifer A.; Pérez-Accino, Jorge; Timothy, Clare; Simpson, Kenneth W.; Salavati Schmitz, Silke (Frontiers in Veterinary Science, 2020)
We describe an unusual case of severe acute protein-losing enteropathy in a dog, which presented with a systemic inflammatory response syndrome. This dog's condition could not be categorized as any well-known canine intestinal condition. Instead, components of several enteropathies like acute hemorrhagic diarrhea syndrome (AHDS), chronic inflammatory enteropathy (CIE), and ulcerative and granulomatous colitis were present. Thorough investigations identified concurrent exocrine pancreatic insufficiency (EPI) and hypocobalaminemia. On histopathology, marked diffuse chronic-active ileitis and ulcerative colitis with fibroplasia and neovascularization were present. Intestinal biopsy cultures identified E.coli and multiresistant Enterococcus spp. The latter was identified as mucosally invasive using fluorescent in situ hybridization (FISH). Protracted clinical signs following the acute presentation required intensive care including enteral and parenteral feeding for a successful outcome, but eventually stabilized with antibiotics and immunosuppressive doses of glucocorticoids. This case highlights a potentially previously unrecognized condition, suspected to be a form of CIE manifesting acutely after bacterial mucosal invasion. In this case, this might have been facilitated by EPI-induced dysbiosis. The use of FISH and mucosal culture in this context provided important clinical information and should be considered more frequently in CIE and non-responsive AHDS.